HUBUNGAN SELF CARE DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS DI PUSKESMAS BIRU- BIRU KECAMATAN SIBIRU-BIRU KABUPATEN DELI SERDANG - Yosafat Barus, Fridella Grace Natalia Tarigan, Tetty Suriany Limbong3 (Universitas Asahan, 2022)
Abstract Diabetes Mellitus is a chronic hyperglycemic state accompanied by various metabolic disorders due to hormonal disorders that cause various chronic complications in the eyes, kidneys, nerves and blood vessels so that it can affect a person's quality of life. Quality of life of patients with diabetes mellitus on average have a poor quality of life due to physical changes. Physical changes felt by patients with diabetes mellitus such as fatigue and disturbances during activities caused by increased blood sugar levels. One way to improve the quality of life is good self-care. The purpose of this study was to identify the relationship between self care and the quality of life of patients with diabetes mellitus at the Biru-Biru Health Center, Sibiru-biru District. This research method uses a correlation design with a sample of 46 respondents at the Biru-Biru Health Center, Sibiru-biru District. The measuring instrument used in this research is a questionnaire. Data analysis was performed using the chi-square test with (p=0.002). The results of this study indicate that there is a relationship between self care and the quality of life of patients with diabetes mellitus at the Biru-Biru Health Center, Sibiru-biru District. It is hoped that patients will be able to further improve self-care so that the quality of life is better. Keywords: Self Care, Quality of Life for Diabetes Mellitus Patients